GaN HEMT for High-performance Applications: A Revolutionary Technology - Pattnaik, Geeta; Mohapatra, Meryleen (Recent Advances in Electrical & Electronic Engineering, 2024)
Background: The upsurge in the field of radio frequency power electronics has led to the involvement of wide bandgap semiconductor materials because of their potential characteristics in achieving high breakdown voltage, output power density, and frequency. III-V group materials of the periodic table have proven to be the best candidates for achieving this goal. Among all the available combinations of group III-V semiconductor materials, gallium nitride (GaN), having a band gap of 3.4eV, has gradually started gaining the confidence to become the next-generation material to fulfill these requirements. Objective: Considering the various advantages provided by GaN, it is widely used in AlGaN/GaN HEMTs (High Electron Mobility Transistors) as their fundamental materials. This work aimed to review the structure, operation, and polarization mechanisms influencing the HEMT device, different types of GaN HEMT, and the various process technologies for developing the device. Methods: Various available methods to obtain an enhancement type GaN HEMT are discussed in the study. It also covers the recent developments and various techniques to improve the performance and device linearity of GaN HEMT. Conclusion: Despite the advantages and continuous improvement exhibited by the GaN HEMT technology, it faces several reliability issues, leading to degradation of device performance. In this study, we review various reliability issues and ways to mitigate them. Moreover, several application domains are also discussed, where GaN HEMTs have proven their capability. It also focuses on reviewing and compiling the various aspects related to the GaN HEMT, thus providing all necessary information.
Keywords: wireless communication applications